KEARIFAN LOKAL BUGIS DALAM AL-QUR’AN: TELAAH MAKNA “DUAMI KUALA SAPPO, UNGANNA PANASAE NA BELONA KANUKUE” - Latif, Abdul; Rifa'in, Aswar (Ma'had Aly As'adiyah Sengkang, 2025)
This article discusses the relationship between the local wisdom of the Bugis community, particularly the traditional advice (pappaseng ogi)